2018
DOI: 10.1186/s13073-018-0576-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-genetic determination of maternal and neonatal immune mediators during pregnancy

Abstract: BackgroundThe immune system plays a fundamental role in development during pregnancy and early life. Alterations in circulating maternal and neonatal immune mediators have been associated with pregnancy complications as well as susceptibility to autoimmune and neurodevelopmental conditions in later life. Evidence suggests that the immune system in adults not only responds to environmental stimulation but is also under strong genetic control.MethodsThis is the first genetic study of > 700 mother-infant pairs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 63 publications
1
36
0
1
Order By: Relevance
“…Bloodspots have been successfully used to determine early life exposures including Vitamin D [ 57 ], perfluorinated chemicals [ 58 ], and endocrine-disrupting chemicals [ 59 ]. Similarly, bloodspots have been used to evaluate outcome measures such as immune function [ 60 , 61 ], thyroid hormones [ 62 ] and insulin concentration [ 63 ]. Epigenome-wide and targeted patterns have also been assessed recently using bloodspots.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodspots have been successfully used to determine early life exposures including Vitamin D [ 57 ], perfluorinated chemicals [ 58 ], and endocrine-disrupting chemicals [ 59 ]. Similarly, bloodspots have been used to evaluate outcome measures such as immune function [ 60 , 61 ], thyroid hormones [ 62 ] and insulin concentration [ 63 ]. Epigenome-wide and targeted patterns have also been assessed recently using bloodspots.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies describe the first steps towards understanding early life immune system development [ 5 , 6 ]. Olin et al [ 5 ] found that early immune system development followed a stereotypic pattern in pre-term and term children, while Traglia et al [ 6 ] compared maternal and fetal contributors to the early life immune system. Both studies made use of high-throughput technologies to measure multiple factors simultaneously.…”
Section: Recent Advances In the Study Of Early Immune System Developmmentioning
confidence: 99%
“…For example, high levels of interleukin (IL)-6, IL-1, IL-8, and tumor necrosis factor (TNF) is predictive of pre-term birth [ 8 ] and type I interferons are essential for host resistance against fetal Zika virus infection in a mouse model [ 9 ]. Traglia et al [ 6 ] focused on the heritability of cytokine and chemokine levels between mothers and infants by conducting the first genome-wide study of immune regulators in infants and mothers simultaneously. Several cytokine and chemokine levels were measured in more than 700 mother–infant pairs and the genome-wide single nucleotide polymorphism-based heritability of each was calculated to find loci that contribute to their levels.…”
Section: Recent Advances In the Study Of Early Immune System Developmmentioning
confidence: 99%
See 2 more Smart Citations